Awareness of vesicovaginal fistula among health workers in some health facilities of Zamfara state, Northwest Nigeria - Mohammed Mawaida, Abdullahi; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; Azad, Abul Kalam; Baba, T. M. (University of Salerno, 2017)
The prevalence of obstetric fistula in Nigeria was found by 2008 National Demographic Health Survey (NDHS) to be 0.4%, suggesting there are approximately 150,000 women of reproductive age currently living with, or who have previously had, obstetric fistula. Fistula prevalence is higher in Northern than in Southern Nigerian zones. For instance, the prevalence of fistula in North Central Nigeria is 0.8%, followed by 0.5% in the North East and 0.3% in North West Nigeria. This study aimed at understanding the knowledge and level of understanding of Health workers in some selected hospitals and clinics in Zamfara State, North West Nigeria. The study was both a descriptive cross sectional and qualitative study of health personnel working in some health facilities in Zamfara State to gain an insight of their understanding and practice about vesicovaginal fistula (VVF) which is a common obstetric and maternal health complication among women in Nigeria during or after delivery. 68.3% of the respondents were females while 31.7% were males. There is no specialist consultant or fistula surgeon among the health personnel interviewed as only 11.7% of them were medical doctors while the remaining are nurses, midwives or community health extension workers. On their knowledge of fistula, 97.6% of them have heard of VVF, and 87% of them were of the opinion that early marriage causes complications during delivery or giving birth. Also 88% of them were aware of VVF as one of the problems associated with early girl-child marriage while only 61% of them knew that obstructed or delayed labour causes VVF. It is important to train and equip the lower cadre health and clinic personnel on VVF and how to prevent it as the management of VVF requires a specialized knowledge and expertise.